BIBLIOMETRIC ANALYSIS THE ROLE OF ISLAMIC PSYCHOLOGY BASED ON QUR'AN IN OVERCOMING ANXIETY AND IMPROVING MENTAL HEALTH AMONG WOMEN - Hartafan, Azmil Iman; Nirwana AN, Andri; Marheni, Cut Linda (Universitas Muhammadiyah Surakarta, 2024)
This study aims to conduct a bibliometric analysis related to the role of Islamic psychology in overcoming anxiety (Anxiety) and improving mental health among women. Bibliometric analysis techniques were used to explore all publications indexed in the Scopus database and the data obtained were analyzed using excel, R-studio and VOS viewer. This research method involves searching and analyzing scientific articles related to Islamic psychology such as, keywords, number of publications per year, main data information, number of citations, productive researchers, and place of publication related to this research, to provide an understanding of the development and impact of research in this field. The results of the bibliometric analysis show that the role of Islamic psychology in overcoming (Anxiety) and improving women's mental health has been the subject of increasing research in recent years as well as a significant increase in the number of publications in this field. the limitations of this study are only taking datasets or meta data on publications indexed on Scopus. Other national and international databases were not taken into account in this study. This study presents a brief overview of the literature accessible to researchers and provides recommendations for future research.